Relaciones políticas del Cuerno de África con los países MENA - Mbiavanga Ajú, Miguel (European Institute of the Mediterranean (IEMed), Afkar/Ideas Issue No.72, 2024)
While the Middle East and North Africa (MENA) States are relatively stable, countries in the Horn of Africa (HoA) continue to be characterized by conflicts, protracted instability and geopolitical tensions. This article assesses the political relations between the Horn of Africa and countries of the MENA region, such as Gulf monarchies, Turkey, Egypt, and Iran given the underlying security implications. The assessment is informed by a review of historical and cultural enumerations in political negotiations, economic, and social interactions between two distinct but deeply connected regions. It is argued that the nature of relationships and the dynamics of the connections require a foresight outlook in reworking the MENA-HoA dealings, in a way that is alternately beneficial in the advancement of strategic, collective and shared common interests of the countries concerned. Ultimately, the State actors involved on both sides of the Arabian Peninsula have been shaping each other’s foreign policy in an unprecedented manner with global implications.